Effect of Lateral Walls on Peristaltic Flow through an Asymmetric Rectangular Duct - Kh. S. Mekheimer; S. Z.-A. Husseny; A. I. Abd el Lateef (Applied Bionics and Biomechanics)
Peristaltic transport of an incompressible viscous fluid due to an asymmetric waves propagating on the horizontal sidewalls of a rectangular duct is studied under long-wavelength and low-Reynolds number assumptions. The peristaltic wave train on the walls have different amplitudes and phase. The flow is investigated in a wave frame of reference moving with velocity of the wave. The effect of aspect ratio, phase difference, varying channel width and wave amplitudes on the pumping characteristics and trapping phenomena are discussed in detail. The results are compared to with those corresponding to Poiseuille flow.